Codyn: An r package of community dynamics metrics. Issue 10 (18th May 2016) - Hallett, Lauren M.; Jones, Sydney K.; MacDonald, A. Andrew M.; Jones, Matthew B.; Flynn, Dan F. B.; Ripplinger, Julie; Slaughter, Peter; Gries, Corinna; Collins, Scott L.
Summary: New analytical tools applied to long‐term data demonstrate that ecological communities are highly dynamic over time. We developed an r package, library("codyn"), to help ecologists easily implement these metrics and gain broader insights into ecological community dynamics. library("codyn") provides temporal diversity indices and community stability metrics. All functions are designed to be easily implemented over multiple replicates. Temporal diversity indices include species turnover, mean rank shifts and rate of community change over time. Community stability metrics calculate overall stability and patterns of species covariance and synchrony over time, and include a null‐modelling method to test significance. Finally, library("codyn") contains vignettes that describe methods and reproduce figures from published papers to help users contextualize and apply functions to their own data.